2020
DOI: 10.1088/1748-9326/ab8093
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variability of tropical cyclone genesis frequency in western North Pacific and South Pacific ocean basins

Abstract: Variability of tropical cyclone (TC) genesis frequency in the western North Pacific and South Pacific ocean basins in the interdecadal scale is studied. It is demonstrated that the TC genesis frequency in these ocean basins experienced an abrupt decrease near the end of the 20th century. The decreased occurrence of TC genesis in the two recent decades is mainly located in the low-latitude regions at the eastern side of the two ocean basins. It is also shown that a significant part of the decreased TC genesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…S2 and S3, respectively, in the online supplemental material. Actually, the fact that the total number of TC events in the postpeak season experienced a significant decrease has been extensively studied (Hsu et al 2014;Shan and Yu 2020a). It may also be demonstrated that there are nearly no TC events belonging to the C2 type in the postpeak season.…”
Section: Variation Of Prevailing Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…S2 and S3, respectively, in the online supplemental material. Actually, the fact that the total number of TC events in the postpeak season experienced a significant decrease has been extensively studied (Hsu et al 2014;Shan and Yu 2020a). It may also be demonstrated that there are nearly no TC events belonging to the C2 type in the postpeak season.…”
Section: Variation Of Prevailing Typesmentioning
confidence: 99%
“…In this study, we try to relate the variability of the TC landfalls in China or the variability of the TC occurrence frequency over the WNP ocean basin to the development of a La Niña-like sea surface warming pattern after the end of twentieth century (Liu and Chan 2013;Hsu et al 2014;Shan and Yu 2020a). In Fig.…”
Section: Effect Of La Niña-like Sea Surface Warmingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the horizontal distribution of Pacific SST anomalies is the key factor for WNP typhoon activities (e.g., Choi et al., 2015; Guo & Tan, 2018; Hu et al., 2018; H. M. Kim et al., 2011; Shan & Yu, 2020; R. Wu et al., 2019; J. Zhao, Zhan, & Wang, 2018). Thus, we turn our attention to the potential impacts of Pacific SST change now.…”
Section: Resultsmentioning
confidence: 99%
“…Although the MT activity linked with the PDO has little influence on the shift of the mean TC formation latitude, the number of TCs that form over the WNP experienced an interdecadal decrease during the end of the twentieth century (Yumoto and Matsuura 2001;Chan 2005;Huangfu et al 2017;Shan and Yu 2020). Not only the TC formation number, but the frequency of intense typhoon occurrence also exhibits decadal to multidecadal variations related to the PDO, since the favorable dynamic conditions (e.g., weak Fig.…”
Section: Two Natural Modes Of the Mt And Its Influences On The Location Of Tc Formationmentioning
confidence: 99%